Stigma Experienced by Families of Children with Autism Spectrum Disorder in Urban Areas: A Phenomenological Study - Cau Kim Jiu; Sri Ariyanti (Talenta Publisher, 2026)
Parents of a child with Autism Spectrum Disorder (ASD) may be stigmatized as families are sometimes penalised by behaviours that are different from those displayed by usually developing children. Such stigma may be link to emotional difficulties, social isolation and experienced lower family quality of life, further emphasising the need to consider the form of stigma and the factors influencing them in their context. The purpose of this qualitative phenomenological study was to make an exploration of the types of stigma that families raising children with ASD in Urban settings experience. Participants: Qualitative data were drawn from semi-structured face-to-face interviews (N = 28) of parents, siblings and grandparent(s) at home, school and a therapy center. The analysis was carried out using qualitative content analysis and the validity of the data was established through prolonged engagement, triangulation, member checking and consultation with experts. It found 5 stigma themes: Physical, internal, public, cultural and label. In summary, urban families with children diagnosed with ASD are faced with multiple persistent forms of stigma that affect their emotional health and sense of social wellbeing. Hence, there is an imminent need for intensive public education, culturally appropriate awareness drives and increased advocacy from health care providers to reduce stigmas and change social dynamics in a favourable manner. Keyword: Autism Spectrum Disorder, Family Stigma, Urban Population, Phenomenology